Rationalised prescribing for community acquired pneumonia: a closed loop audit. Issue 4 (1st October 2000) - Clements, Helena; Stephenson, Terence; Gabriel, Vanessa; Harrison, Timothy; Millar, Michael; Smyth, Alan; Tong, William; Linton, Chris J
Abstract : AIMS: To audit the management of community acquired pneumonia before and after the introduction of a protocol. To determine the aetiology of pneumonia using routine investigations and polymerase chain reaction (PCR). METHODS: Retrospective and prospective audit following the introduction of a management protocol. Prospective cases were investigated routinely and with PCR on blood and nasopharyngeal aspirate. RESULTS: There was a significant increase in rational prescribing following introduction of the protocol with 75% of children receiving intravenous penicillin or erythromycin compared with 26% beforehand. Of 89 children in the prospective group, 51 microbiological diagnoses were achieved in 48 children. Seven children had Streptococcus pneumoniae infection, 14 had Mycoplasma infection, six had pertussis, and one had Chlamydia pneumoniae infection. Twenty three children had a viral cause of which respiratory syncytial virus was commonest. CONCLUSIONS: Introduction of the protocol led to improved prescribing. PCR increased the diagnostic yield and the results support the management protocol.